A method to detect and quantify long chain fatty acids in liquid and solid samples and its relevance to understand anaerobic digestion of lipids - Neves, L. (2007)
A method for long chain fatty acids (LCFA) extraction, identification and further quantification by capillary gas chromatography was developed and its application to liquid and solid samples demonstrated. Linear calibration curves (r² between 0.997 and 1.000) were constructed for C12 to C18 LCFA, in the range from 25 to 1270 mg/L. All the acids were quantified in a single run using pentadecanoic acid (C15:0) as internal standard with response factors ranging from 0.79 to 1.09. Relative standard deviation values lower than 15% and mean LCFA recoveries above 90% were obtained. After validation, the usefulness of this method was demonstrated in a cow manure digester receiving pulses of an industrial effluent containing high lipid content. The knowledge obtained with the application of this method can contribute to a better understanding of LCFA adsorption and degradation processes that occur during the anaerobic digestion of lipids.